1988
DOI: 10.1007/bf00005940
|View full text |Cite
|
Sign up to set email alerts
|

Plankton community cycling and recovery after drought — dynamics in a basin on a flood plain

Abstract: Lake Merrimajeel, a shallow swamp, is part of the Murray-Darling, a flood plain river system with high plankton diversity. It fluctuates drastically in water level and often dries out. The dynamics and seasonality of zooplankton in the face of these fluctuations and the effects of a total drawdown and refilling were monitored between February 1977 and January 1980. During this period thirty species of rotifers, thirty four of microcrustacea and several other species were recorded. Despite erratic fluctuations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
1
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 35 publications
(38 reference statements)
4
22
1
1
Order By: Relevance
“…Abundant food for waterbirds usually coincides with flooding patterns or rainfall, producing wetland habitat (Maher 1984;Maher and Carpenter 1984;Briggs et al 1985b;Crome and Carpenter 1988;Kingsford 1989b;Boulton and Lloyd 1992;Puckridge et al 2000). In contrast, food abundance is low during dry periods (Kingsford 1989a;Whitehead and Saalfeld 2000) and waterbirds may take whatever foods are available, disperse or die.…”
Section: Feeding Ecologymentioning
confidence: 99%
“…Abundant food for waterbirds usually coincides with flooding patterns or rainfall, producing wetland habitat (Maher 1984;Maher and Carpenter 1984;Briggs et al 1985b;Crome and Carpenter 1988;Kingsford 1989b;Boulton and Lloyd 1992;Puckridge et al 2000). In contrast, food abundance is low during dry periods (Kingsford 1989a;Whitehead and Saalfeld 2000) and waterbirds may take whatever foods are available, disperse or die.…”
Section: Feeding Ecologymentioning
confidence: 99%
“…Whilst a number of studies in Australia have established that high densities of meiofauna can occur in floodplain habitats during both high and low flow conditions (e.g. Crome, 1986;Crome and Carpenter, 1988;Tan and Shiel, 1993), only a few studies have examined densities within the main channel of lowland rivers (Shiel et al, 1982;Shiel, 1985;Kobayashi et al, 1998). Shiel et al (1982) and Shiel (1985) found low average densities of zooplankton (<150 individuals l À1 ) in the pelagic zone across a number of seasons in the Murray and Darling Rivers, whereas average densities up to 803 individuals l À1 occurred in the tidal Hawkesbury-Nepean River system (Kobayashi et al, 1998).…”
Section: Introductionmentioning
confidence: 98%
“…No segundo período, as chuvas intensas propiciaram elevação do volume do reservatório e circulação da água, um processo de diluição foi detectado, em função do decréscimo nas concentrações de clorofila-a, matéria particulada e nutrientes, com maior número de espécies de algas constituídas por Crytophyceae e Cyanophyceae. Em relação ao zooplâncton, predador do fitoplâncton, Crome & Carpenter (1988) observaram aumento das densidades e de diversidade das espécies na fase final de um processo de seca quando as águas eram turvas em lago de planície de inundação na Austrália. Essas elevações foram atribuídas não ao efeito de concentração pela redução do volume do ambiente, mas à diminuição da pressão de predação, por alta taxa de mortalidade dos predadores.…”
unclassified